2009
DOI: 10.1007/s00430-009-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response to Mycobacterium tuberculosis-specific antigen culture filtrate protein-10 in south India

Abstract: The Mycobacterium tuberculosis (M. tuberculosis)-specific culture filtrate protein-10 (CFP-10) is highly recognized by M. tuberculosis infected subjects. In the present study, the proliferative response and IFN-gamma secretion was found for C-terminal peptides of the protein (Cfp6(51-70), Cfp7(61-80), Cfp8(71-90), and Cfp9(81-100)). The alleles HLA DRB1 *04 and HLA DRB1 *10 recognized the C-terminal peptides Cfp7, Cfp8, and Cfp9 in HHC. Cfp6 was predominantly recognized by the alleles HLA DRB1 *03 and HLA DRB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…On the other hand, we found that the number of single (either IFN-or TNF-) cytokine-secreting T cells did not differ between these two groups, except the PPD-specific TNF-. This study results corroborates with our earlier observations [23,24]. PPD-specific TNF-was significantly higher in TB patients compared to HHC.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, we found that the number of single (either IFN-or TNF-) cytokine-secreting T cells did not differ between these two groups, except the PPD-specific TNF-. This study results corroborates with our earlier observations [23,24]. PPD-specific TNF-was significantly higher in TB patients compared to HHC.…”
Section: Discussionsupporting
confidence: 93%
“…Papers have been devoted to improvement of laboratory diagnoses of Mycobacterium infections [53], on vaccination-relevant studies regarding immunocellular reactions to M. tuberculosis [54], as well as to current concepts on the development of a vaccine [55,56]. Of distinct interest, related work has led to progress on vaccine development against buruli ulcer disease [57].…”
Section: Pathogen Variation and Host Response In Infectious Diseasesmentioning
confidence: 99%